2015
DOI: 10.4103/0973-029x.157200
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of myofibroblasts in oral squamous cell carcinoma using H1 calponin: An immunohistochemical study

Abstract: Background:Oral squamous cell carcinoma (OSCC) is the most common malignancy of the oral mucosa. Stromal myofibroblasts play an important role in tumor invasion and metastasis, due to its ability to modify the extracellular matrix. The purpose of this study was to evaluate and compare the presence of myofibroblasts in normal mucosa, early invasive carcinoma and different grades of OSCC.Materials and Methods:The study included the archival tissues of 18 OSCC of well, moderate and poorly differentiated grades, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
1
Order By: Relevance
“…Consistent with the results of our investigation, the presence of stromal myofibroblasts was statistically different in grades I , II, and III of OSCC. Contrary to the present study, Parasad et al, Etemad Moghadam et al, and Ganesan K et al did not observed any significant difference in the distribution of myofibroblasts among different grades of OSCC (11)(12)(13).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Consistent with the results of our investigation, the presence of stromal myofibroblasts was statistically different in grades I , II, and III of OSCC. Contrary to the present study, Parasad et al, Etemad Moghadam et al, and Ganesan K et al did not observed any significant difference in the distribution of myofibroblasts among different grades of OSCC (11)(12)(13).…”
Section: Discussioncontrasting
confidence: 99%
“…The results also showed that most of the specimens had scores 1 and 2 in the superficial layers of OSCC. In contrast, most of the specimens had score 3 in the deep promoting cancer-associated fibroblasts (12).…”
Section: Resultsmentioning
confidence: 90%
“…The expression of muscle tissue associated genes in samples from lymph node positive patients but not in OSCC cell lines suggests that such gene signature may derive from myofibroblasts, which are absent in normal oral mucosa and constitute the OSCC stroma [ 29 ].…”
Section: Resultsmentioning
confidence: 99%